Application of Ultrasonic and Coating Material Thickness Testing on Post-Fire Steel Construction - Citra, Zel; Antonius; Biantoro, Agung Wahyudi (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Steel has advantages over other construction materials, including flexibility and processing time. Steel has better elasticity and relatively faster processing time compared to reinforced concrete. However, the weakness is that steel is also very susceptible to temperature changes. If a steel material experiences an increase in temperature, for example, if it is directly exposed to fire, its yield and tensile strength will decrease drastically. This can cause the function of the steel material as a structural element to change. In early 2023, a fire occurred in a steel construction tower used for animal feed processing, PT. XYZ in the Lampung area. As a result of the fire, there is a concern about the risk of structural failure, which could cause worker fatalities in the building. So, it is necessary to test the thickness of steel tower structural elements such as columns, beams, and bracing using the Non-Destructive Test method with an Ultrasonic Material Gauge and Material Coating Thickness. The test samples were taken in as many as 20 samples with the test structure including column elements, beam elements, and bracing at each level or elevation of the fire-affected floor. Test sample include WF200X100X5,5x8, WF250X125X6X9, WF300X150X6,5X9, WF400X200X8X13, HB400X400X13X21 and Pipe Ø6”. The results of the post-fire steel structure measurement, the thickness of columns, beams, and bracing from 20 samples, showed that 95% still met the thickness tolerance of 0.7 mm- 1.2 mm based on the SNI 07-0329-2005. The thickness of the post-fire coating, 95% steel structural coating, did not meet the standards below 240mm. Only 5% met the minimum coating thickness standards, such as pipe bracing Ø6